Urban noise slows down the antipredator reaction of Eurasian Magpies - Abou-Zeid, Farah; Benedetti, Yanina; Siretckaia, Anastasiia; Morelli, Federico (Frontiers in Ecology and Evolution, 2024)
Urban areas are known to have high levels of noise pollution, which can impact an animal's antipredator behavior. Noise can either distract the animal or mask the sounds of a predator, increasing the animal's vulnerability to predation. However, the prey may increase vigilance in noisier environments, thus reducing energy and time spent on other activities. Alert Distance (AD) refers to the distance at which an animal becomes alert to a potential predator approaching. Flight Initiation Distance (FID) is the distance from the potential predator at which the animal flees. We studied the impact of ambient noise pollution on the AD and a corrected FID (FID/AD) of Eurasian Magpies (Pica pica) using a field investigator as a potential predator walking towards birds at a constant speed. We found that the noise level did not affect the AD. Still, noise had a negative effect on the Eurasian Magpies' FID/ADs, suggesting that noise may slow their reaction to a potential threat but not their ability to detect it. Thus, our research highlights that urban noise pollution can increase individual vulnerability to predation, even when predators are still detectable. Ambient noise may distract the bird by diverting some of its limited attention and causing a delayed response to the predators. Alternatively, noise could be masking auditory cues that would have otherwise been added together with visual cues to cause an enhanced response. More research is necessary to understand the effects of noise pollution on the antipredator behavior of birds in urban areas, taking into account the specific strategies and adaptations of each species.